Positive plate as well as electrochemical device and electronic equipment comprising positive plate

By introducing metal oxides containing oxygen vacancies into the positive electrode material layer of the lithium ion battery, the problems of low conductivity and structural distortion of lithium manganese iron phosphate positive electrode material are solved, and lower diaphragm resistance, lower high-temperature gas production growth and better cycle stability and capacity performance are achieved.

CN119742319AActive Publication Date: 2025-04-01ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411975571.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-01
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The existing lithium-ion battery cathode material lithium manganese iron phosphate has low in intrinsic conductivity, and there is a serious ginger-Taylor effect in manganese during charging and discharging, resulting in structural distortion and lithium ion diffusion obstacles, which in turn limits its electrochemical performance.

Method used

The metal oxide containing oxygen-containing vacant positions is introduced into the positive electrode material layer and dispersed in the positive electrode active material to improve the conductivity of the positive electrode sheet, reduce interfacial side reactions, reduce gas production, and improve battery stability.

Benefits of technology

By introducing metal oxides containing oxygen vacancies, the diaphragm resistance of the positive electrode sheet is reduced, the growth of high-temperature gas production is reduced, and the circulation stability and capacity performance of lithium-ion batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221367640000151
    Figure BDA0005221367640000151
  • Figure BDA0005221367640000161
    Figure BDA0005221367640000161
  • Figure BDA0005221367640000162
    Figure BDA0005221367640000162
Patent Text Reader

Abstract

The invention discloses a positive plate as well as an electrochemical device and electronic equipment comprising the positive plate. The positive plate comprises a positive current collector; a positive electrode material layer is arranged on at least one surface of the positive electrode current collector; the positive electrode material layer comprises a positive electrode active material and a metal oxide containing oxygen vacancies, and the metal oxide containing oxygen vacancies is dispersed in the positive electrode active material. The diaphragm resistance of the positive plate is relatively low, the high-temperature gas production increase of an electrochemical device (especially a lithium ion battery) prepared by adopting the positive plate is relatively low, and excellent capacity performance and cycling stability can be considered at the same time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a positive electrode sheet and an electrochemical device and an electronic device containing the positive electrode sheet. Background Art

[0002] Lithium manganese iron phosphate (LiMnFePO4) is a lithium-ion battery cathode material with the same olivine structure as lithium iron phosphate (LiFePO4). It has excellent structural stability and the corresponding battery has excellent safety. Its voltage platform (4.1V) is 0.7V higher than that of lithium iron phosphate. When the other battery designs of the two are the same, it can increase the battery energy density by 20%. Therefore, it is a new type of lithium battery material that can take into account both high energy density and high safety. However, the intrinsic conductivity of lithium manganese phosphate is lower (<10-10S / cm), and manganese has a more serious Jan-Taylor effect during the charge and discharge process, which leads to structural distortion, hinders the diffusion of lithium ions, and ultimately causes its electrochemical performance to fail to be brought into play.

[0003] Energy density, cycle stability, low impedance, and increased high-temperature gas production during high-temperature storage have always been the focus of attention in improving the performance of lithium-ion battery positive electrode materials. However, in actual production applications, it is difficult to take all of them into account. Therefore, how to improve the above performance of lithium-ion battery positive electrodes has always been the focus of the industry. Summary of the invention

[0004] In order to solve the above problems existing in lithium-ion batteries in the prior art, the present invention provides a positive electrode sheet and an electrochemical device and an electronic device containing the same. The positive electrode sheet has a low membrane resistance, and the electrochemical device (especially a lithium-ion battery) prepared using the positive electrode sheet has a low high-temperature gas production growth, and can take into account excellent capacity performance and cycle stability.

[0005] To achieve the above objectives, the present invention adopts the following technical solutions.

[0006] In a first aspect, the present invention provides a positive electrode sheet comprising a positive electrode current collector; a positive electrode material layer is disposed on at least one surface of the positive electrode current collector; the positive electrode material layer comprises a positive electrode active material and a metal oxide containing oxygen vacancies, and the metal oxide containing oxygen vacancies is dispersed in the positive electrode active material.

[0007] In a second aspect, the present invention provides an electrochemical device comprising the positive electrode sheet as described above.

[0008] In a third aspect, the present invention provides an electronic device comprising the electrochemical device as described above.

[0009] The positive and progressive effects of the present invention are:

[0010] In the present invention, metal oxides containing oxygen vacancies are introduced into the positive electrode material layer and dispersed in the positive electrode active material, so that the membrane resistance of the obtained positive electrode sheet is low, and the high-temperature gas production growth of the electrochemical device (especially lithium-ion battery) prepared using the positive electrode sheet is low, and excellent cycle stability and capacity performance can be taken into account. DETAILED DESCRIPTION

[0011] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0012] Positive electrode

[0013] In the positive electrode sheet provided in the first aspect of the present invention, it includes a positive electrode collector; a positive electrode material layer is arranged on at least one surface of the positive electrode collector; the positive electrode material layer includes a positive electrode active material and a metal oxide containing oxygen vacancies, and the metal oxide containing oxygen vacancies is dispersed in the positive electrode active material.

[0014] In the present invention, a metal oxide containing oxygen vacancies is introduced into the positive electrode material layer, and the metal oxide containing oxygen vacancies is dispersed in the positive electrode active material. The advantages are: on the one hand, the metal oxide containing oxygen vacancies has ultra-high conductivity, which can improve the conductivity of the electrode sheet, improve the specific capacity and cycle stability; on the other hand, the oxygen vacancies in the metal oxide containing oxygen vacancies can absorb oxygen anions generated by the positive electrode active material, reduce interfacial side reactions, reduce gas production, and improve battery stability.

[0015] In some embodiments, the metal oxide containing oxygen vacancies comprises CeO 2-a 、TiO 2-a , WO 3-a 、Al2O 3-a and ZrO 2-a One or more of, preferably CeO 2-a , wherein 0<a≤0.65, a is preferably 0.1-0.2, and a is, for example, 0.4 or 0.65.

[0016] In some embodiments, the content of the metal oxide containing oxygen vacancies is 0.2%-2%, for example, 0.5% or 1%, where the percentage is the mass percentage of the positive electrode material layer.

[0017] In some specific embodiments, the metal oxide containing oxygen vacancies is CeO 1.8 .

[0018] In some specific embodiments, the metal oxide containing oxygen vacancies is CeO 1.4 .

[0019] In some specific embodiments, the metal oxide containing oxygen vacancies is CeO 1.9 .

[0020] In some specific embodiments, the metal oxide containing oxygen vacancies is CeO 1.35 .

[0021] In some specific embodiments, the metal oxide containing oxygen vacancies is CeO 1.8 and TiO 1.8 .

[0022] In some specific embodiments, the metal oxide containing oxygen vacancies is WO 2.8 .

[0023] In some specific embodiments, the metal oxide containing oxygen vacancies is TiO 1.8 .

[0024] In some specific embodiments, the metal oxide containing oxygen vacancies is CeO 1.6 .

[0025] In the present invention, the CeO 2-a The preparation method may include the following steps: dissolving cerium nitrate or cerium chloride in water to obtain an aqueous solution, wherein the concentration of the aqueous solution is 0.5-2 mol / L, adjusting the pH value of the aqueous solution to 2-3, filtering and drying to obtain a precipitate, and calcining the precipitate in an air atmosphere to obtain CeO 2-a ; wherein the calcination temperature is 400-600°C, the calcination time is 2-10h, and the oxygen partial pressure of the air atmosphere is 5-15kPa.

[0026] In the present invention, the WO 2.8 The preparation method may include the following steps: dissolving ammonium tungstate in water to obtain a mixture, filtering and drying to obtain a precipitate, and calcining the precipitate in an air atmosphere to obtain WO 2.8 ; wherein the concentration of the mixture is 1 mol / L, the calcination temperature is 1100°C, the calcination time is 4h, and the oxygen partial pressure of the air atmosphere is 14kPa.

[0027] In the present invention, the TiO 1.8 The preparation method may include the following steps: dissolving titanyl sulfate in water to obtain a mixture, filtering and drying to obtain a precipitate, and calcining the precipitate in an air atmosphere to obtain TiO 1.8 ; wherein the concentration of the mixture is 1 mol / L, the calcination temperature is 1000°C, the calcination time is 4h, and the oxygen partial pressure of the air atmosphere is 14kPa.

[0028] In some optional embodiments, the metal oxide containing oxygen vacancies has a Dv50 particle size of 5 nm-1 μm, such as 0.1-0.3 μm, such as 0.15 μm or 0.2 μm.

[0029] In some optional embodiments, the mass ratio of the positive electrode active material to the metal oxide containing oxygen vacancies is (90-190):1, preferably (90-99.9):1, more preferably (96-99.5):1, for example 95:1.

[0030] In some optional embodiments, the positive electrode active material includes lithium manganese iron phosphate and / or a ternary positive electrode material.

[0031] In some preferred embodiments, the positive electrode active material is lithium manganese iron phosphate and a ternary positive electrode material, and the mass ratio of the lithium manganese iron phosphate to the ternary positive electrode material is (40-60): (60-40).

[0032] In the present invention, the chemical formula of the lithium manganese iron phosphate can be Li z Mn x Fe 1-x PO4, wherein z is 0.9-1.1, preferably 1.0-1.03, and x is 0-1, preferably 0.6-0.8.

[0033] In the present invention, the lithium manganese iron phosphate may be doped with heteroatoms, and the heteroatoms include one or more of Ti, Mg, Zr, V, Nb, Mo, W, Al, Ni and Co.

[0034] In the present invention, the lithium manganese iron phosphate may further include an outer coating layer, which is, for example, one or both of a carbon layer and a metal oxide layer; the metal oxide layer preferably includes one or more of aluminum oxide, tungsten oxide, titanium oxide, zirconium oxide, molybdenum oxide and zinc oxide.

[0035] In the present invention, the Dv50 particle size of the lithium manganese iron phosphate may be 0.3-2 μm.

[0036] In the present invention, the chemical formula of the ternary cathode material can be LiNi x Co y Mn 1-x-y O2, wherein 0.6≤x<1, and y is 0-0.2.

[0037] In the present invention, the ternary cathode material may be doped with heteroatoms, and the heteroatoms include one or more of Ti, Mg, Zr, V, Nb, Mo, W and Al.

[0038] In the present invention, the ternary positive electrode material may further include an outer coating layer, which is, for example, one or both of a carbon layer and a metal oxide layer; the metal oxide layer preferably includes one or more of aluminum oxide, tungsten oxide, titanium oxide, zirconium oxide, molybdenum oxide and zinc oxide.

[0039] In the present invention, the ternary positive electrode material may be a single crystal material.

[0040] In the present invention, the Dv50 particle size of the ternary positive electrode material may be 2-6 μm.

[0041] In some specific embodiments, the positive electrode active material includes LiMn 0.6 Fe 0.4 PO4 and LiNi 0.6 Co 0.1 Mn 0.3 O2, LiMn 0.6 Fe 0.4 The Dv50 particle size of PO4 is 0.67 μm, and the LiNi 0.6 Co 0.1 Mn 0.3 The Dv50 particle size of O2 is 3.58 μm; the LiMn 0.6 Fe 0.4 PO4 and LiNi 0.6 Co 0.1 Mn 0.3 The mass ratio of O2 is 50:50, 40:60 or 60:40.

[0042] In some preferred embodiments, the content of the positive electrode active material is greater than 80%, where the percentage is the mass percentage of the positive electrode material layer.

[0043] In some preferred embodiments, the positive electrode material layer includes LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and a metal oxide containing oxygen vacancies, wherein the metal oxide containing oxygen vacancies is, for example, CeO 1.8 、CeO 1.4 、CeO 1.9 、CeO 1.6 、CeO 1.35 、TiO 1.8 and WO 2.8 One or more of .

[0044] In some specific embodiments, the positive electrode material layer includes LiMn 0.6 Fe 0.4 PO4、LiNi0.6 Co 0.1 Mn 0.3 O2 and CeO 1.8 , the LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.8 The mass ratio is 47.5:47.5:1.

[0045] In some specific embodiments, the positive electrode material layer includes LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.8 , the LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.8 The mass ratio is 47.5:47.5:0.5.

[0046] In some specific embodiments, the positive electrode material layer includes LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.4 , the LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.4 The mass ratio is 47.5:47.5:1.

[0047] In some specific embodiments, the positive electrode material layer includes LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.9 , the LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.9 The mass ratio is 47.5:47.5:1.

[0048] In some specific embodiments, the positive electrode material layer includes LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.35 , the LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.35 The mass ratio is 47.5:47.5:1.

[0049] In some specific embodiments, the positive electrode material layer includes LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.8 , the LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.8 The mass ratio is 49.95:49.95:1.

[0050] In some specific embodiments, the positive electrode material layer includes LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.8 , the LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.8 The mass ratio is 45:45:1.

[0051] In some specific embodiments, the positive electrode material layer includes LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2、CeO 1.8 and TiO 1.8 , the LiMn 0.6 Fe0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2、CeO 1.8 and TiO 1.8 The mass ratio is 47.5:47.5:0.8:0.2.

[0052] In some specific embodiments, the positive electrode material layer includes LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and WO 2.8 , the LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and WO 2.8 The mass ratio is 47.5:47.5:1.

[0053] In some specific embodiments, the positive electrode material layer includes LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and TiO 1.8 , the LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and TiO 1.8 The mass ratio is 47.5:47.5:1.

[0054] In some specific embodiments, the positive electrode material layer includes LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.6 , the LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.6 The mass ratio is 47.5:47.5:1.

[0055] In some specific embodiments, the positive electrode material layer includes LiMn 0.6 Fe0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.8 , the LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.8 The mass ratio is 38:57:1.

[0056] In some specific embodiments, the positive electrode material layer includes LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.8 , the LiMn 0.6 Fe 0.4 PO4、LiNi 0.6 Co 0.1 Mn 0.3 O2 and CeO 1.8 The mass ratio is 57:38:1.

[0057] In the present invention, the positive electrode material layer may further include a conductive agent, the content of the conductive agent is 1%-3%, for example, 1.5%, where the percentage is the mass percentage of the positive electrode material layer.

[0058] In the present invention, the conductive agent may be a conventional conductive material in the art, preferably including one or more of conductive carbon black (SuperP), acetylene black, carbon nanotubes (CNT), graphene and vapor grown carbon fiber reinforcement (VGCF), such as CNT and SP.

[0059] In the present invention, the positive electrode material layer may further include a binder, and the content of the binder is 1%-4%, for example, 2.5%, where the percentage is the mass percentage of the positive electrode material layer.

[0060] In the present invention, the binder may be a binder commonly used in the art, preferably including one or both of polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), such as PVDF.

[0061] In some embodiments, in the positive electrode material layer, the mass ratio of the positive electrode active material, the metal oxide containing oxygen vacancies, the conductive agent and the binder is (90-99.9):(0.2-2):(1-3):(1-4).

[0062] In some embodiments, the positive electrode sheet is prepared by the following method: the components of the positive electrode material layer are fully stirred and mixed in a solvent to obtain a positive electrode slurry which is coated on at least one surface of the positive electrode collector, dried, cold pressed, and cut.

[0063] Wherein, the solid content of the positive electrode slurry is preferably 55%-60%.

[0064] Wherein, the viscosity of the positive electrode slurry is preferably 2000-4000 Pa·s.

[0065] Electrochemical Devices

[0066] In the electrochemical device provided in the second aspect of the present invention, it includes the positive electrode sheet as described above.

[0067] In the present invention, the electrochemical device is preferably a battery.

[0068] In some optional embodiments, the electrochemical device is a lithium ion battery; the lithium ion battery further comprises a negative electrode sheet, a separator and an electrolyte.

[0069] Negative plate

[0070] In the present invention, the negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer, and the negative electrode material layer is disposed on at least one surface of the negative electrode current collector.

[0071] In the present invention, the negative electrode material in the negative electrode material layer can be a negative electrode material conventionally used in the art, preferably including one or more of artificial graphite, natural graphite, soft carbon, hard carbon, mesophase carbon microbeads, silicon dioxide and silicon-carbon materials, such as artificial graphite.

[0072] In some embodiments, the negative electrode material layer further includes a thickener.

[0073] The addition of the thickener can increase the system viscosity of the components in the negative electrode slurry, and the thickener can be a conventional thickener used in the art for preparing negative electrode sheets, such as sodium carboxymethyl cellulose (CMC).

[0074] In some embodiments, the negative electrode material layer further includes a conductive agent.

[0075] There are no particular restrictions on the conductive agent, as long as it has conductivity and does not cause chemical changes in the battery. For example, specific examples include: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as conductive carbon black (Super P), carbon nanotubes (CNT), acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black or carbon fiber; metal powder or metal fiber, such as copper, nickel, aluminum or silver; conductive whiskers, such as zinc oxide whiskers or potassium titanate whiskers; conductive metal oxides, such as titanium dioxide; or conductive polymers, such as polyphenylene derivatives.

[0076] In some specific embodiments, the conductive agent in the negative electrode material layer is acetylene black.

[0077] In some embodiments, the negative electrode material layer further includes a binder.

[0078] Among them, the type of the binder is not particularly limited, and can be selected from polyvinylidene fluoride, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid (PAA), ethylene-propylene-diene terpolymer and its sulfonate, styrene-butadiene rubber (SBR), fluororubber and various copolymers, such as SBR.

[0079] In some specific embodiments, in the negative electrode material layer, the mass ratio of the negative electrode material, the conductive agent, the binder and the thickener is 96.4:1:1.4:1.2.

[0080] In the present invention, the negative electrode current collector may be a conventional negative electrode current collector in the art. The negative electrode current collector is used as a substrate to support the negative electrode material layer, and is generally a metal foil having a thickness of 3-500 microns. There is no particular restriction on the material, as long as it has high conductivity and does not produce chemical reactions in the secondary battery system. For example, it can be a foil formed after surface treatment of nickel, titanium, aluminum, nickel, silver, stainless steel, carbon, etc. The negative electrode current collector is generally a smooth surface, but fine lines may also be formed on its surface to increase the adhesion between the negative electrode material layer and the current collector. In addition to the foil, the negative electrode current collector may also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. Generally, the negative electrode current collector is copper foil.

[0081] In some embodiments, the method for preparing the negative electrode sheet comprises the following steps: thoroughly stirring and mixing the components of the negative electrode material layer in a solvent to obtain a negative electrode slurry which is applied on at least one surface of the negative electrode current collector, dried, cold pressed, and cut.

[0082] Diaphragm

[0083] In the present invention, the diaphragm may be a diaphragm conventionally used in the art.

[0084] In some optional embodiments, the separator may be a polypropylene (PP) film, a polyethylene (PE) film or a PP / PE / PP porous film, for example, a PP / PE / PP porous film.

[0085] Wherein, the air permeability of the diaphragm may be 180-380s / 100mL.

[0086] Wherein, the porosity of the diaphragm may be 30%-50%.

[0087] Wherein, the thickness of the diaphragm may be 9-18 μm.

[0088] In a specific embodiment, the diaphragm is a polyethylene film; the thickness of the diaphragm is 16 μm; the air permeability of the diaphragm is 230 s / 100 mL; and the porosity of the diaphragm is 40%.

[0089] Electrolyte

[0090] In some embodiments, the electrolyte may be an electrolyte conventionally used for batteries in the art, generally including a non-aqueous solvent, a lithium salt, and additives.

[0091] In some embodiments, the preparation method of the lithium-ion battery includes the following steps: stacking the positive electrode sheet, the separator, and the negative electrode sheet in sequence, so that the separator is located between the positive and negative electrode sheets to play an isolating role; then wrapping with an aluminum-plastic film, injecting the electrolyte after drying, and finally preparing a soft-pack battery through packaging, standing, formation and other processes.

[0092] In some embodiments, the capacity of the lithium-ion battery is, for example, 1 Ah.

[0093] Electronic devices

[0094] The electronic device provided in the third aspect of the present invention comprises the electrochemical device as described above.

[0095] Exemplarily, the electronic device described in the present invention may be, but is not limited to, mobile devices (such as mobile phones, tablet computers, laptop computers, video recorders, portable printers / copiers, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems and backup power supplies, etc.

[0096] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0097] The reagents and raw materials used in the present invention are commercially available.

[0098] In the following examples, the specific preparation method of the metal oxide containing oxygen vacancies is as follows:

[0099] (1) Metal oxide CeO containing oxygen vacancies 1.8 The preparation method of (a is 0.2) comprises the following steps:

[0100] Dissolve cerium nitrate in water to obtain an aqueous solution (the concentration of the metal salt is 2 mol / L), add oxalic acid and Ammonia pH Control 2.5, separation and drying to obtain the precipitate, and then high temperature calcination under a certain atmosphere Get CeO 1.8 The calcination temperature was 600°C, the time was 5 h, and the atmosphere was air with an oxygen partial pressure of 14 kPa.

[0101] (2) Metal oxide CeO containing oxygen vacancies 1.4 、CeO 1.9 、CeO 1.35 and CeO 1.6 Preparation method: In the above metal oxide CeO containing oxygen vacancies 1.8 Based on the preparation method, CeO 1.4 、CeO 1.9 、CeO 1.35 and CeO 1.6 In the preparation method of CeO, only the oxygen partial pressure was changed to 7 kPa, 16 kPa, 5 kPa and 10 kPa, and the other conditions were the same as those of CeO 1.8 The preparation method remained consistent.

[0102] (3) Metal oxides containing oxygen vacancies WO 2.8 The preparation method of (a is 0.2) comprises the following steps:

[0103] Ammonium tungstate is dissolved in water to obtain a mixture (the concentration of the metal salt is 1 mol / L), and a precipitate is obtained after separation and drying, and then calcined at high temperature under a certain atmosphere to obtain WO 2.8 The calcination temperature was 1100°C, the time was 4 h, and the atmosphere was air with an oxygen partial pressure of 14 kPa.

[0104] (4) Metal oxides containing oxygen vacancies TiO 1.8 The preparation method of (a is 0.2) comprises the following steps:

[0105] Titanyl sulfate was dissolved in water to obtain a mixture (the concentration of the metal salt was 1 mol / L), and a precipitate was obtained after separation and drying, and then calcined at high temperature under a certain atmosphere to obtain TiO 1.8 The calcination temperature was 1000°C, the time was 4 hours, and the atmosphere was air with an oxygen partial pressure of 14 kPa.

[0106] Example 1

[0107] In this embodiment, the method for preparing the positive electrode sheet includes the following steps:

[0108] Super P, CNT, NMP, and PVDF were first mixed in a mass ratio of 1:0.5:80:2.5, and dispersed and stirred at a rotation speed of 1500 rpm / min for 2 hours to prepare a conductive slurry.

[0109] Afterwards, the positive electrode active material and the metal oxide CeO containing oxygen vacancies 1.8 The conductive slurry was stirred and mixed at a speed of 2000 rpm / min to prepare a positive electrode slurry (solid content of 59%, viscosity of 3570 Pa·s). Then, the prepared slurry was evenly coated on the aluminum foil with a scraper, placed in a blast drying oven, and dried for 30 minutes at 120 degrees Celsius to obtain a pole piece. The slurry formed a positive electrode material layer. Finally, the dried pole piece was rolled (rolled to a compaction of 2.9 g / cc) and cut to make a positive electrode sheet.

[0110] The positive electrode active material in the obtained positive electrode material layer is lithium manganese iron phosphate LiMn 0.6 Fe 0.4 PO4 and single crystal ternary cathode material LiNi 0.6 Co 0.1 Mn 0.3 O2 (mass ratio is 50:50), and the positive electrode active material, metal oxide CeO containing oxygen vacancies 1.8 The mass ratio of Super P, CNT and PVDF is 95:1:1:0.5:2.5, and the mass ratio of lithium manganese iron phosphate, ternary cathode material and CeO 1.8 The Dv50 particle sizes are 0.67μm, 3.58μm and 0.2μm respectively.

[0111] Example 2

[0112] The difference between this embodiment and embodiment 1 is that in the positive electrode material layer, the positive electrode active material, CeO 1.8 The mass ratio of SuperP, CNT and PVDF is 95:0.5:1:0.5:2.5, and the other conditions are consistent with Example 1.

[0113] Example 3

[0114] The difference between this embodiment and embodiment 1 is that in the positive electrode material layer, only CeO 1.8 CeO 1.4 (a is 0.6), CeO 1.4 The Dv50 particle size is 0.2 μm, and the other conditions are consistent with those in Example 1.

[0115] Example 4

[0116] The difference between this embodiment and embodiment 1 is that in the positive electrode material layer, only CeO 1.8 CeO 1.9 (a is 0.1), CeO 1.9 The Dv50 particle size is 0.2 μm, and the other conditions are consistent with those in Example 1.

[0117] Example 5

[0118] The difference between this embodiment and embodiment 1 is that in the positive electrode material layer, only CeO 1.8 CeO 1.35 (a is 0.65), CeO 1.35 The Dv50 particle size is 0.2 μm, and the other conditions are consistent with those in Example 1.

[0119] Example 6

[0120] The difference between this embodiment and embodiment 1 is that in the positive electrode material layer, only CeO 1.8 The Dv50 particle size is 1 μm, and the other conditions are consistent with those in Example 1.

[0121] Example 7

[0122] The difference between this embodiment and embodiment 1 is that in the positive electrode material layer, only CeO 1.8 The Dv50 particle size is 0.3 μm, and the other conditions are consistent with those in Example 1.

[0123] Example 8

[0124] The difference between this embodiment and embodiment 1 is that in the positive electrode material layer, only CeO 1.8 The Dv50 particle size is 0.1 μm, and the other conditions are the same as those in Example 1.

[0125] Example 9

[0126] The difference between this embodiment and embodiment 1 is that in the positive electrode material layer, the positive electrode active material, CeO 1.8 , SuperP, CNT and PVDF is 99.9:1:1:0.5:2.5, and the other conditions are consistent with Example 1.

[0127] Example 10

[0128] The difference between this embodiment and embodiment 1 is that in the positive electrode material layer, the positive electrode active material, CeO 1.8 The mass ratio of SuperP, CNT and PVDF is 90:1:1:0.5:2.5, and the other conditions are consistent with Example 1.

[0129] Embodiment 11

[0130] The difference between this embodiment and embodiment 1 is that in the positive electrode material layer, the metal oxide containing oxygen vacancies also includes TiO 1.8 (Dv50 particle size is 0.2 μm), wherein in the positive electrode material layer, the positive electrode active material, CeO 1.8 、TiO 1.8 The mass ratio of Super P, CNT and PVDF is 95:0.8:0.2:1:0.5:2.5, and the other conditions are consistent with Example 1.

[0131] Example 12

[0132] The difference between this embodiment and embodiment 1 is that WO 2.8 Replace CeO 1.8 , WO 2.8 The Dv50 particle size is 0.15 μm, among which the positive electrode active material, WO 2.8 The mass ratio of Super P, CNT and PVDF is 95:1:1:0.5:2.5, and the other conditions are consistent with Example 1.

[0133] Embodiment 13

[0134] The difference between this embodiment and embodiment 1 is that TiO 1.8 Replace CeO 1.8 , TiO 1.8 The Dv50 particle size is 0.2 μm, and the positive electrode active material, TiO 1.8 The mass ratio of Super P, CNT and PVDF is 95:1:1:0.5:2.5, and the other conditions are consistent with Example 1.

[0135] Embodiment 14

[0136] The difference between this embodiment and embodiment 1 is that in the positive electrode material layer, lithium manganese iron phosphate LiMn 0.6 Fe 0.4 PO4 and ternary cathode material LiNi 0.6 Co 0.1 Mn 0.3 The mass ratio of O2 is 40:60, and the other conditions are consistent with Example 1.

[0137] Embodiment 15

[0138] The difference between this embodiment and embodiment 1 is that in the positive electrode material layer, lithium manganese iron phosphate LiMn 0.6 Fe 0.4 PO4 and ternary cathode material LiNi0.6 Co 0.1 Mn 0.3 The mass ratio of O2 is 60:40, and the other conditions are consistent with Example 1.

[0139] Example 16

[0140] The difference between this embodiment and embodiment 1 is that in the positive electrode material layer, the positive electrode active material is only lithium manganese iron phosphate LiMn 0.6 Fe 0.4 PO4, the other conditions remain the same as in Example 1.

[0141] Embodiment 17

[0142] The difference between this embodiment and embodiment 1 is that in the positive electrode material layer, the positive electrode active material is only the ternary positive electrode material LiNi 0.6 Co 0.1 Mn 0.3 O2, the other conditions are the same as in Example 1.

[0143] Embodiment 18

[0144] The difference between this embodiment and embodiment 1 is that in the positive electrode material layer, only CeO 1.8 CeO 1.6 (a is 0.4), CeO 1.6 The Dv50 particle size is 0.2 μm, and the other conditions are consistent with those in Example 1.

[0145] Comparative Example 1

[0146] The difference between this comparative example and Example 1 is that the positive electrode material layer does not contain CeO 1.8 The mass ratio of the positive electrode active material, Super P, CNT and PVDF is 96:1:0.5:2.5, and the other conditions are consistent with Example 1.

[0147] Comparative Example 2

[0148] The difference between this comparative example and Example 1 is that CeO2 is used to replace CeO in the positive electrode material layer. 1.8 The mass ratio of the positive electrode active material, CeO2, Super P, CNT and PVDF is 95:1:1:0.5:2.5, and the other conditions are consistent with Example 1.

[0149] Some parameters of the positive electrode sheets in the above-mentioned Examples 1-18 and Comparative Examples 1-2 are shown in Table 1.

[0150] Effect Example 1: Film resistance of positive electrode sheet

[0151] The positive electrode sheets in Examples 1-18 and Comparative Examples 1-2 were respectively used to measure the film resistance. The specific test method is as follows:

[0152] Use a punching machine to cut three φ14 small discs from the above positive electrode sheet, measure the thickness of the small discs and record them; use a film resistance meter to test the small discs and record the film resistance.

[0153] The test results are shown in Table 2.

[0154] Effect Example 2 Preparation and Electrochemical Performance Test of Lithium Ion Battery

[0155] Preparation of lithium-ion batteries (soft pack batteries)

[0156] (1) Preparation of negative electrode sheet

[0157] The negative electrode material artificial graphite, the conductive agent acetylene black, the thickener CMC, and the binder SBR are mixed in a mass ratio of 96.4:1:1.2:1.4, and the solvent deionized water is added, and the mixture is fully stirred to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode collector copper foil, and a negative electrode sheet is prepared through drying, cold pressing, and slitting processes.

[0158] (2) Preparation of electrolyte

[0159] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0160] (3) Diaphragm

[0161] A PP / PE / PP porous membrane with a thickness of 16 μm was used as the separator.

[0162] The air permeability of the membrane is 230s / 100mL, and the porosity is 40%.

[0163] (4) Assembly of lithium-ion batteries

[0164] The positive electrode sheets in Examples 1-18 and Comparative Examples 1-2 are respectively used to assemble lithium-ion batteries, and the specific steps are as follows:

[0165] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in sequence, so that the separator is placed between the positive and negative electrode sheets to play a role of isolation. Then, the aluminum plastic film is wrapped, and after drying, the prepared electrolyte is injected. After packaging, standing, forming, and aging, a soft-pack battery with a capacity of 1Ah, that is, a lithium-ion battery, is finally prepared.

[0166] Electrochemical performance test

[0167] The electrochemical performance of the lithium-ion battery just prepared was tested as follows:

[0168] (1) Gram capacity and 500 cycle capacity retention rate at 45°C

[0169] Gram capacity: With a current density of 0.33C and a voltage window of 2.8-4.4V, the battery is activated by charging and discharging three times, and the discharge capacity of the third charge and discharge is tested. Gram capacity = discharge capacity / mass of positive electrode active material.

[0170] High temperature cycle test: The activated battery is charged and discharged for 500 cycles at 1C in the range of 2.8-4.4V at 45℃, and the capacity ratio of the 500th cycle to the 1st cycle is recorded as its capacity retention rate.

[0171] (2) 56-day high-temperature gas production growth rate

[0172] Conduct high temperature storage gas production test:

[0173] The state of charge of the activated battery was adjusted to 100% SOC, and the cell volume at this time was tested by the water displacement method at room temperature, which was recorded as the cell volume V0 on day 0. The battery was then stored in a 60°C constant temperature oven. Every 7 days, the battery was taken out of the oven, left to stand and cooled to room temperature, and the cell volume was tested by the water displacement method. The cell volume (V0) after 56 days was recorded. 56 ). The calculation formula for the growth rate of high-temperature gas production for 56 days is: (V 56 -V0) / V0×100%.

[0174] The above test results are shown in Table 2.

[0175] Table 1

[0176]

[0177]

[0178] Table 2

[0179]

[0180] It can be seen from Table 1 and Table 2 above that in Examples 1-18 of the present invention, the film resistance of the obtained positive electrode sheet can be lower than 23.5Ω, and the 56-day high-temperature gas production growth rate of the prepared electrochemical device (especially lithium-ion battery) can be lower than 30%. On this basis, the capacity retention rate of 500 cycles at 45°C can be higher than 88%, and the gram capacity can reach more than 135mAh / g.

[0181] In the present invention, by introducing metal oxides containing oxygen vacancies into the positive electrode material layer, the positive electrode sheet containing the metal oxides has good conductivity, the prepared electrochemical device (especially lithium-ion battery) has low high-temperature gas production growth for 56 days, and can take into account excellent cycle stability and capacity performance. However, if the positive electrode sheet does not include metal oxides containing oxygen vacancies, the above effects cannot be taken into account.

[0182] Compared with Example 1, in Comparative Example 1, the positive electrode sheet does not contain CeO 1.8 The film resistance of the positive electrode sheet was significantly improved, the 56-day high-temperature gas production growth rate of the prepared lithium-ion battery was significantly worse, and the 500-cycle capacity retention rate and gram capacity at 45°C were also poor.

[0183] Compared with Example 1, in Comparative Example 2, the positive electrode sheet contains CeO2 but not CeO 1.8 The film resistance of the positive electrode sheet deteriorated significantly, the 56-day high-temperature gas production growth rate of the prepared lithium-ion battery increased significantly, and the 500-cycle capacity retention rate and gram capacity at 45°C were poor.

[0184] In Examples 16-17, lithium iron manganese phosphate or ternary positive electrode materials are used alone as positive electrode active materials. Although compared with the metal oxide containing oxygen vacancies in Comparative Examples 1-2, the use of lithium iron manganese phosphate or ternary positive electrode materials as positive electrode active materials is also advantageous. However, compared with the use of lithium iron manganese phosphate and ternary positive electrode materials as positive electrode active materials in Example 1, the film resistance of the obtained positive electrode sheet is lower, and the obtained lithium-ion battery either has a reduced capacity retention rate of 500 cycles at 45°C, a reduced growth rate of high-temperature gas production for 56 days, or a reduced capacity per gram. This may be because the electronic conductivity of pure lithium iron manganese phosphate is low, the conductivity is good, but the polarization is large, which is not conducive to the battery capacity; and the pure ternary positive electrode material is easy to release oxygen anions, resulting in serious battery gas production, which ultimately leads to poor battery cycle performance and storage performance. When lithium iron manganese phosphate and ternary positive electrode materials are used as positive electrode active materials in Example 1, on the basis of metal oxides containing oxygen vacancies, the advantages of both lithium iron manganese phosphate and ternary positive electrode materials can be fully utilized to further improve the effect. It should be noted that: although the above embodiments of the present invention do not reflect the presence of doping elements M (which may include one or more of Ti, Mg, Zr, V, Nb, Mo, W, Al, Ni and Co) and / or an outer coating layer in positive electrode active materials such as lithium iron manganese phosphate and ternary positive electrode materials, in fact, the above-mentioned lithium iron manganese phosphate and ternary positive electrode materials with doping elements or outer coating layers as positive electrode active materials are still applicable to the technical solution of the present invention, and the technical effect of the present invention can be achieved.

[0185] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A positive electrode sheet, characterized in that: It comprises a positive electrode current collector; a positive electrode material layer is arranged on at least one surface of the positive electrode current collector; the positive electrode material layer comprises a positive electrode active material and a metal oxide containing oxygen vacancies, and the metal oxide containing oxygen vacancies is dispersed in the positive electrode active material.

2. The positive electrode sheet according to claim 1, characterized in that: The metal oxide containing oxygen vacancies includes CeO 2-a 、TiO 2-a , WO 3-a 、Al2O 3-a and ZrO 2-a One or more of , wherein 0<a≤0.

65.

3. The positive electrode sheet according to claim 1, characterized in that: The Dv50 particle size of the metal oxide containing oxygen vacancies is 5 nm-1 μm.

4. The positive electrode sheet according to claim 1, characterized in that: The metal oxide containing oxygen vacancies satisfies one or two of the following conditions ab: a. The mass ratio of the positive electrode active material to the metal oxide containing oxygen vacancies is (90-190):1; b. The content of the metal oxide containing oxygen vacancies is 0.2%-2%, where the percentage is the mass percentage of the positive electrode material layer.

5. The positive electrode sheet according to claim 1, characterized in that: The positive electrode active material includes lithium manganese iron phosphate and / or a ternary positive electrode material.

6. The positive electrode sheet according to claim 5, characterized in that: The positive electrode active material is lithium manganese iron phosphate and a ternary positive electrode material, and the mass ratio of the lithium manganese iron phosphate to the ternary positive electrode material is (40-60): (60-40).

7. The positive electrode sheet according to claim 5, characterized in that: The lithium manganese iron phosphate and the ternary positive electrode material meet one or more of the following conditions ai: a. The chemical formula of the lithium manganese iron phosphate is Li z Mn x Fe 1-x PO4, where z is 0.9-1.1 and x is 0-1; b. The lithium manganese iron phosphate is doped with heteroatoms, wherein the heteroatoms include one or more of Ti, Mg, Zr, V, Nb, Mo, W, Al, Ni and Co; c. The lithium manganese iron phosphate also includes an outer coating layer; d. The Dv50 particle size of the lithium manganese iron phosphate is 0.3-2 μm; e. The chemical formula of the ternary positive electrode material is LiNi x Co y Mn 1-x-y O2, where 0.6≤x<1, y is 0-0.2; f. The ternary cathode material is doped with heteroatoms, wherein the heteroatoms include one or more of Ti, Mg, Zr, V, Nb, Mo, W and Al; g. The ternary cathode material further includes an outer coating layer; h. The ternary cathode material is a single crystal material; i. The Dv50 particle size of the ternary positive electrode material is 2-6 μm.

8. The positive electrode sheet according to claim 1, characterized in that: The positive electrode material layer satisfies one or more of the following conditions ac: a. The content of the positive electrode active material is more than 80%, where the percentage is the mass percentage of the positive electrode material layer; b. The positive electrode material layer further includes a conductive agent, the content of which is 1%-3%, where the percentage is the mass percentage of the positive electrode material layer; c. The positive electrode material layer further includes a binder, the content of the binder is 1%-4%, and the percentage is the mass percentage of the positive electrode material layer.

9. An electrochemical device, characterized in that: It comprises the positive electrode sheet as described in any one of claims 1 to 8.

10. An electronic device, characterized in that: It comprises the electrochemical device as claimed in claim 9.

Citation Information

Patent Citations

  • Battery positive electrode material, positive pole plate comprising same, battery negative electrode material, negative pole plate comprising battery negative electrode material, lithium ion battery and electrode paste

    CN110212182A

  • Preparation of vacancy cerium oxide loaded bimetallic nanoparticles and application of vacancy cerium oxide loaded bimetallic nanoparticles in electrocatalytic reduction of nitrate

    CN115287693A

  • Oxygen vacancy tungsten oxide coated positive electrode material, preparation method and lithium battery

    CN116387495A

  • Cathode active material, secondary battery and preparation method

    CN116504961A

  • Positive electrode for lithium secondary battery comprising positive electrode additive

    CN117121223A